Assessment of nickel leaching phenomena from landfill waste mixed paving block for eco-friendly field application. (15th December 2016) - Haque, M. Aminul
Abstract: Nowadays landfill solid waste management is the prime concern in all over the world because it is the potential source of greenhouse gas emission. Side by side heavy metals and toxic chemicals intrusion into the food chain through the soil as well as the surrounding surface water body or percolates groundwater causing water contamination. Such contaminations of water resources possess substantial risk to the local natural environment at landfill sites. As a result, it becomes an attractive proposition to reduce the decomposed solid waste load at landfill sites through recycling the waste as an eco-friendly product. This paper aims to analyze how to make eco-friend paving block from landfill waste by widely used solidification/stabilization technique. It also examines encapsulation of toxic nickel ion within the constructed monolithic paving block specimens by employing the standard mass transfer-static leaching test in immersion leachant. This study reveals the cement to fine aggregate mixing ratio 1:2 whereas 30% waste is substituted of the total volume of fine aggregate, as optimum for eco-friendly release rate of nickel along with satisfies the required mechanical performance for paving block design. In addition, the analytical results of some leaching parameters namely effective diffusion coefficient, leachability index and slope of the regression line of cumulative amount leached also shows the satisfactory level for nickel release content under the same proportion. Furthermore, contaminant transport Models are successfully calibrated and justifies against the statistical point of view for interpreting the nickel releasing profile followed by the Model parameters estimation with 95% confidence interval with high accuracy and tiny error. The findings of the current study might show the path of a potential solution to utilize of landfill decomposed waste materials in economical paving block construction and at the same time helps in reducing disposal concerns. Highlights: Ni(II) content was observed in landfill waste and leachate at toxic level. Solidification/stabilization technique was adopted to encapsulate Ni(II). Landfill waste was recycled for producing eco-friendly paving block construction. Leaching parameters were analyzed for assessing the green product as eco-friendly. Leachate Models were calibrated for interpreting the Ni(II) leaching phenomena.